The problem of measuring and disclosing the human capital in the financial statements A study on the national enterprise for public works materials in Constantine - debache, amira (Milev Journal of Research and Studies, 2016)
This study seeks to identify the constraints facing the National enterprise for public Works materials in Constantine in the processes of measurement and disclosure of human capital, where there are many obstacles to the process of measurement and disclosure of human capital that became one of the important things in the enterprise. To achieve the objectives of the study and answer its questions a Questionnaire was designed to collect information, and it was distributed to individuals working in departments and the services of finance and accounting in the enterprise, and were processed using the statistical program SPSS